2020
DOI: 10.1302/1863-2548.14.200132
|View full text |Cite
|
Sign up to set email alerts
|

Poor delineation of labrum and acetabular surface on arthrogram is a predictor of early failure of closed reduction in children aged six to 24 months with developmental dysplasia of the hip

Abstract: Purpose The objective of this study was to explore the predictors for failed reduction in children with developmental dysplasia of the hip (DDH) managed by arthrogram, closed reduction (CR) and spica cast immobilization. Methods We retrospectively reviewed the clinical data of patients with DDH treated by CR and cast immobilization (2015-2020), including age, sex, affected side, presence/absence of an ossific nucleus, International Hip Dysplasia Institute classification, the delineation of labrum and acetabula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Many researchers have previously investigated the use of MDP in hip arthrogram. Yuan et al (26) investigated the clinical data of 173 patients (187 hips) with DDH treated with closed reduction and measured MDP to predict reduction failure. They showed that the risk of reduction failure was significantly increased when MDP was >6 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have previously investigated the use of MDP in hip arthrogram. Yuan et al (26) investigated the clinical data of 173 patients (187 hips) with DDH treated with closed reduction and measured MDP to predict reduction failure. They showed that the risk of reduction failure was significantly increased when MDP was >6 mm.…”
Section: Discussionmentioning
confidence: 99%
“…By arthrography and MRI, Hattori [ 24 ] and Kim [ 26 ] found that obvious soft tissue insertion in the hip joint, widening of the medial contrast cistern, and LCC hypertrophy would increase the probability of CR failure, thus increasing the need for open surgery, even if surgical treatment cannot achieve a good prognosis. Yuan et al [ 27 ] found that poor delineation of the labrum and acetabular surface during arthrogram predicted failure of CR in children with DDH, and medial dye pool distance ≥6 mm significantly increased the risk of CR failure. However, the studies by Severin [ 12 ] and Aoki [ 28 ] have shown that the inverted labrum can be gradually shaped and returned to a normal shape after CR without affecting the final acetabular-head alignment.…”
Section: Discussionmentioning
confidence: 99%